Pengaruh alat peraga memorize trigonometri fingers terhadap motivasi dan hasil belajar siswa SMA Negeri 1 Ngronggot - Wahyuni, Dwi; Nurwiani, Nurwiani; Masruroh, Faridatul (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2024)
The research aims to analyze: Whether or not there is an influence of using the Memorize Trigonometry Fingers teaching aid on the motivation and learning outcomes of class X students at SMA Negeri 1 Ngronggot. Quantitative research, carried out using the normality test, homogeneity test, t test, Mann Whitney U test, r test, Spearman's rho correlation test and determination. Student population of SMA Negeri 1 Ngronggot class X. Sample of students in class X-3 and X-2. Focuses on Trigonometry of special angles in the first quadrant. Hypothesis research results: There is an effectiveness of using the Memorize Trigonometry Fingers teaching aid on learning motivation of 1.6%, including very weak. There is an influence of using the Memorize Trigonometry Fingers teaching aid on learning motivation of r = 0.126, including a low level of relationship. The direction of the relationship is positive, meaning that if the motivation value of the experimental class is high then the motivation value of the control class is high, and vice versa. Hypothesis research results: There is an effectiveness of using the Memorize Trigonometry Fingers teaching aid on learning outcomes of 0.0001%, including very weak. There is an influence of using the Memorize Trigonometry Fingers teaching aid on learning outcomes of -0.567, including a moderate level of relationship. The direction of the relationship is negative, meaning that if the experimental class learning outcomes are high then the control class learning outcomes are low, and vice versa.